A comparative analysis of urban and rural construction land use change and driving forces: Implications for urban–rural coordination development in Wuhan, Central China. (June 2015) - Liu, Yaolin; Luo, Ti; Liu, Zhongqiu; Kong, Xuesong; Li, Jiwei; Tan, Ronghui
Abstract: This paper explores the spatial–temporal changes of urban–rural construction land use and its anthropogenic driving forces in Wuhan from 1996 to 2009. The vector maps and data from two National Land Investigations in China, socio-economic information from government departments are used, and land use dynamic models and landscape metrics with mathematical statistical method are applied. The outcomes show the expansion of urban–rural construction land, which is extremely rapid that the amount of cultivated land drastically dwindled, the aggregation of urban construction land strengthened, and the fragmentation of rural construction land aggravated. The urban–rural difference of construction land use changes exists in the regional disparity between the inner city and the outer city of Wuhan. During the study period in Wuhan, the quantity and structure changes of urban–rural construction land in the outer city play a decisive role for the change trends of the total city. Societal and economic factors, which include demographic change, economic growth, living standards, and policies, are closely related to the pattern of urban–rural construction land use. Significant regional and urban–rural differences exist on the driving mechanism between the inner city and the outer city of Wuhan. The smooth implementation of urban–rural coordination development can be achieved by allocating the rational scale of urban–rural construction land, optimizing city–town–village spatial system, improving the efficiency of urban–rural land utilization and restructuring urban–rural production, living and ecological spaces. Highlights: The expansion of urban/rural construction land leads to the drastic change of urban/rural landscape pattern respectively. The disparity of urban-rural construction land use changes coexists with regional differences. Anthropogenic factors are closely related to the pattern of urban-rural construction land use. Implementations for urban-rural coordination development can be obtained from the analyses of land use change in Wuhan.